16S rDNA BASED PHYLOGENY OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS ISOLATES FROM THE PUS SPECIMENS - S. GANESH MANIKANDAN; C. LAKSHMINARASIMHAN; N.THAJUDDIN; M. GOVINDARAJAN (The Bioscan, 2011)
The genomic comparison of the MRSA isolates from pus sample has been done with that of the standard strains from GenBank. The rapid identification of bacteria in clinical samples is very important for patient management and antimicrobial therapies. Methicillin Resistant Staphylococcus aureus (MRSA) isolated from pus samples of clinical patients. Isolated MRSA named as SMKV-1 and SMKV-2 grown properly using with Oxoid CM3 Nutrient agar medium. Genomic DNA from above strains was isolated and 16S rDNA were amplified using suitable primers. The amplified 16S rDNA sequences have been deposited in the GenBank (DQ 306890 and DQ 306891) and selected 16S rDNA sequences of the genus Staphylococcus from the database were used to study the phylogenetic relationship with the present MRSA isolates. mecA gene appeared on 310 bp region on agarose gel electrophoresis. In the present study we found that the MRSA isolates were 100% similar to GenBank strains.